THE TRADITIONS OF BEING ZULLISONAIN IN THE WORKS OF MULLA SHAMS SHAWQI (World Economics and Finance Bulletin, 2024)
The author states about the works of Mulla Shams Shavqi who is the representative of Namangan literature and studies the tradition of zullisonain in his works and tries to highlight some of his literary works by analyzing today’s content. He compares the expressions in mukhammas with the mystical meaning of the example
Keywords: Analyzes; ghazells; genre; sufism